2023
DOI: 10.1002/tox.23752
|View full text |Cite
|
Sign up to set email alerts
|

A novel mechanism of cannabidiol in suppressing ovarian cancer through LAIR‐1 mediated mitochondrial dysfunction and apoptosis

Abstract: Cannabidiol (CBD) is a nonpsychoactive cannabinoid compound. It has been shown that CBD can inhibit the proliferation of ovarian cancer cells, but the underlying specific mechanism is unclear. We previously presented the first evidence for the expression of leukocyte-associated immunoglobulin-like receptor 1 (LAIR-1), a member of the immunosuppressive receptor family, in ovarian cancer cells. In the present study, we investigated the mechanism by which CBD inhibits the growth of SKOV3 and CAOV3 ovarian cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 52 publications
(103 reference statements)
0
9
0
Order By: Relevance
“…CBD is highly appreciated as a product with many beneficial pharmacological effects, including antioxidant and anti-tumor properties. 33,37,43 And CBD has been shown to be a protective effect in several kidney injuries. 44,45 To investigate the potential mechanisms of renal injury caused by PFOS exposure and the protective effects of CBD, we developed an in vivo and in vitro PFOS exposure model and a CBD treatment model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CBD is highly appreciated as a product with many beneficial pharmacological effects, including antioxidant and anti-tumor properties. 33,37,43 And CBD has been shown to be a protective effect in several kidney injuries. 44,45 To investigate the potential mechanisms of renal injury caused by PFOS exposure and the protective effects of CBD, we developed an in vivo and in vitro PFOS exposure model and a CBD treatment model.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to explore the mechanisms of PFOS nephrotoxicity and seek medical candidates or antagonists. CBD is highly appreciated as a product with many beneficial pharmacological effects, including antioxidant and anti‐tumor properties 33,37,43 . And CBD has been shown to be a protective effect in several kidney injuries 44,45 .…”
Section: Discussionmentioning
confidence: 99%
“…OC poses a serious threat to the lives of patients. [18][19][20][21][22] Currently, the most common way to treat OC is surgical resection and adjuvant chemotherapy. 23 However, the prognosis of OC patients remains unsatisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…OC poses a serious threat to the lives of patients 18–22 . Currently, the most common way to treat OC is surgical resection and adjuvant chemotherapy 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with Laetrile and ‘CBD oil’ that contains multiple molecules altered expression of genes in low-grade serous ovarian cancer in a single patient case-study ( Barrie et al, 2019 ). In addition, it was shown in vitro and in vivo that CBD inhibits OC cell growth ( Ma et al, 2023 ). Based on cell line studies it was suggested that it inhibits cell growth by disrupting the LAIR-1-mediated interference with PI3K/AKT/mTOR pathway and mitochondrial bioenergy metabolism ( Ma et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%